Strengthening English Language Learning through Artificial Intelligence-Based Mobile Applications: A Comparative Study in Formal and Informal Contexts - Nurmala, Ira; Reza, Ali; Apriansyah Hutagalung, Carli; Pattiasina , Petrus Jacob; Malintang, Jimmy (International Journal of Language and Ubiquitous Learning, 2024)
Background. AI-based mobile applications are revolutionizing language learning by offering personalized, adaptable tools. Their impact differs across various learning environments, prompting the necessity for a comparative study to understand these variances better. Purpose. This study aims to compare the effectiveness of AI-based mobile applications for English language learning in formal classroom settings versus informal self-study environments. The goal is to determine how these tools perform across different contexts and identify the optimal conditions for their use. Method. A comparative study was conducted involving high school and university students in formal educational settings and adult learners in informal self-study settings. Over three months, participants utilized AI-based language learning applications. Data collection involved pre- and post-tests to measure learning outcomes, alongside surveys and interviews to gauge user experiences and preferences. Results. Analysis revealed significant improvements in both learning environments, with formal settings showing a 12% increase in test scores and informal settings an 8% increase. Students in formal settings more frequently engaged with interactive features, whereas informal learners gravitated towards self-study tools. Engagement and interaction levels were notably higher in formal educational settings compared to informal ones. Conclusion. AI-based mobile applications significantly enhance English language learning, particularly in structured, formal environments. The findings underscore the importance of tailoring these tools to fit different learning contexts. While both formal and informal settings benefit from these applications, formal education environments seem to leverage their interactive features more effectively, resulting in higher engagement and better learning outcomes. This study highlights the need for educators and developers to consider context-specific strategies to maximize the benefits of AI-based language learning tools.